Building and Validation of Scale to measure the Perception of Social Innovation Ecosystems - Nespolo, Daniele; Fachinelli, Ana Cristina; Giacomello, Cíntia Paese (Revue internationale d'intelligence economique, 2019)
Understanding the criteria for the formation and development of social innovation ecosystems is crucial to establish appropriate strategies for their creation, maintenance and expansion. In this regard, strategies should be focused on social development actions, mainly supported by governments and members of the society. Silva, Sá and Spinosa (2019) reinforce that the interaction between government, industry and academia, coined in the literature as Triple Helix, by Etzkowitz and Leydesdorff (2000), has been increasingly recognized for driving the transformation of scientific and technological results into economic results. According to a study by Schaffers et. al (2012), the progress towards the understanding of the intersection between urban economy, innovation networks, technology platforms, services and their applications, collective intelligence and innovation theories themselves is one of the challenges for innovation. This understanding can help scholars, governments and professionals to explore new directions and produce knowledge and solutions to make cities smarter. This study aimed to carry on a previous study by Nespolo and Fachinelli (2017) as well as build and validate a scale to measure the perception of social innovation ecosystems.
Number: 2
Keywords: Mesure de la perception; Réservé UdeM; Triple Helix